1982
DOI: 10.1111/j.1600-0528.1982.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between caries prevalence and incidence among adolescents

Abstract: The purpose of this study was 1) to determine the strength and direction of the association between caries prevalence at 13-14 years of age and subsequent caries increments and 2) to assess the goodness of fit of a multivariate model to caries increments from age 13 1/2 to 20. Two sets of data were used. The first consisted of treatment records for 114 children from an incremental dental care program. They were divided into high and low caries prevalence groups at ages 13 and 14 and 2-and 3-year caries increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…The estimated net effect of a unit increase in the age 17 caries count was associated with 0.22 higher mean AdjCI 17‐23 . This is consistent with the findings by Alm et al [22], Haugejorden & Birkheland [23], and Rise et al [24], which all showed a positive association between caries experience in adulthood and previous caries experience during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 93%
“…The estimated net effect of a unit increase in the age 17 caries count was associated with 0.22 higher mean AdjCI 17‐23 . This is consistent with the findings by Alm et al [22], Haugejorden & Birkheland [23], and Rise et al [24], which all showed a positive association between caries experience in adulthood and previous caries experience during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that non-modifiable factors in the present analyses, i.e., person level and surface level net cavitated caries increment count from 9 to 13, were positively and significantly associated with net cavitated caries incidence and net cavitated caries increment count from 13 to 17, respectively. This emphasizes the consistent evidence of positive association of caries with previous caries experience/baseline caries prevalence observed in adolescents (Alm et al, 2012;Haugejorden & Birkheland, 2007, Rise et al, 1982 and younger age groups. Another important finding was the negative association between the modifiable factor of frequency of foods predominant in fiber and natural sugar (vegetables) and both net cavitated caries incidence and net cavitated caries increment count, respectively.…”
Section: Chapter 6 Conclusionsupporting
confidence: 73%
“…Risk indicators associated with caries in adolescents have been documented in cross-sectional studies including those from Ditmyer et al, 2008, andDitmyer et al, 2010. On the other hand, non-modifiable risk factors are those that cannot be modified by an intervention and include variables such as previous caries experience, early childhood dietary behaviors, demographic factors such as age, sex etc. A few longitudinal studies have been done on non-modifiable risk factors such as previous caries experience and/or previous dietary exposures (Alm et al, 2012, Rise et al, 1982. Overall, the evidence based on longitudinal data for both modifiable and non-modifiable risk factors for caries in adolescents are sparse and provide inconsistent results, likely due to differences in analytical designs, study populations, age distributions, and risk factor definitions.…”
Section: Department Of Health and Human Servicesmentioning
confidence: 99%
“…It has long been known that there is an association between caries experience in the primary dentition and the DMFS index values in the permanent dention of the same subject [Hill ct al., 1967;Poulsen and Holm, 1980;Alaluusua et al, 1987;ter Pelkwijk et al, 1990]. At a group level, caries experience has also been shown to correlate with future caries increment [Birkeland et al, 1976;Rise et al, 1982]. Since prediction of caries increment on the basis of the S .…”
mentioning
confidence: 99%